Anemia and Inflammation in ST-Segment Elevation Myocardial Infarction. (June 2015) - Zhang, Enyuan; Li, Zhenyu; Che, Jingjin; Chen, Xin; Qin, Tiantian; Tong, Qing; Zhao, Weiwei; Li, Guangping
Abstract: Background: To investigate the factors predicting the onset of major adverse cardiovascular events (MACEs) after primary percutaneous coronary intervention for ST-segment elevation myocardial infarction (STEMI) patients. Methods: Two hundred forty-eight STEMI patients (61.4 ± 10.8 years, 186 men) who underwent successful primary percutaneous coronary intervention were enrolled. Patients were followed-up for 1 year. Univariate, multivariate analyses, and receiver operating characteristic curve analysis were performed to determine the factors predicting MACEs. Results: There were 36 patients (14.5%) who experienced MACEs in the follow-up period. Multivariate logistic regression analysis demonstrated that hemoglobin (HgB) (odds ratio = 0.972; 95% CI, 0.948–0.998; P = 0.033), neutrophil/lymphocyte ratio (NLR) (odds ratio = 1.511; 95% CI, 1.148–1.987; P = 0.003), Global Registry of Acute Coronary Event score, and postprocedure left ventricular ejection fraction (LVEF) were independent predictors of MACEs. Further subgroup analysis showed higher NLR (>8.61), Global Registry of Acute Coronary Event score (>167) and lower HgB (<131 g/L) all show superior predictive value for patients with relatively higher LVEF (>48%); moreover, the c-statistic of NLR and HgB both exceed 0.7. However, among patients with lower LVEF (⩽48%), higher NLR and lower HgB lost the ability for predicting 1 year MACEs independently. In addition, abnormally higher NLR (>8) could predict 1-month MACEs efficiently. Conclusions: In summary, among STEMI patients, elevated NLR, decreased HgB level on admission both predicted 1-year MACEs independently, especially for those with relatively preserved LVEF (>48%). Besides, abnormally higher NLR on admission should attract their attention for short-term MACEs.